“I lock myself in my room and cry in frustration”: an analysis of adolescent behaviors of child-to-parent violence - Arias-Rivera, Shirley; Lorence, Barbara; Maya, Jesus (Frontiers in Psychiatry, 2025)
Child-to-parent violence (CPV) encompasses behaviors such as hitting, insulting, or threatening parents. Over the past decade, the number of CPV cases has increased significantly. While previous research has largely focused on classifying CPV behaviors and examining their causes, there is limited investigation into what happens immediately after CPV episodes. This study aims to describe the behaviors of adolescents following violent actions in both mild and severe cases of CPV. A randomized sample of 1,067 Spanish adolescents, participating in a national CPV project, was studied using the Child-to-Parent Aggression Questionnaire. Among them, 410 adolescents (41.91% boys and 57.84% girls) reported engaging in some form of CPV behavior in the past year, and 47 adolescents met the criteria for severe and repeated CPV. Specifically, 26 adolescents exhibited psychological and 27 exhibited physical CPV toward their mother, while 21 adolescents exhibited psychological and 15 physical CPV toward their father. Adolescents were asked, “What do you do after?” Following thematic analysis, adolescents’ responses were categorized into 6 themes and 17 sub-themes in mild cases. A possible sequence in adolescents’ responses was identified, divided into three phases. In the first phase, adolescents felt bad after their violent behavior, expressed remorse, reflected on it, and sought a safe place. In the second phase, apologizing to parents was the most common response, reported by 70.52% of adolescents. Finally, in the third phase, in addition to apologizing, adolescents attempted to talk with their parents, gave them a hug, or committed to not repeating the behavior. In contrast, 8% of adolescents normalized their behavior, joked about it, or justified their actions. In severe cases, most subthemes were consistent with those observed in mild CPV cases. However, in contrast to milder cases, severe cases showed a lower percentage of adolescents who felt bad or apologized and a higher proportion who normalized, avoided talking about, or justified their violent actions (23.4% of adolescents with severe CPV). This study highlights practical implications for interventions, such as the importance of helping them express their emotions, recognize the harm caused, identify safe spaces, people, or activities, and support them in the process of apologizing.